Effect of integrated nutrient management on productivity, energy-use efficiency and economics of soybean (Glycine max-wheat (Triticum aestivum) cropping system - Billore, S D; Vyas, A K; Joshi, O P (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 2000-01 and 2001-02 at Indore, Madhya Pradesh, to find out the effect of conjunctive use of organic, i e soybean [Glycine max(L.) Merrill] residue and farmyard manure, and inorganic sources (straight NPK fertilizers) of nutrients in soybean- wheat (Triticum aestivum L . emend. Fiori. and Paol.) cropping system. The conjunctive application of soybean residue @ 5 tonnes/ha + farmyard manure @ 5 tonnes/ha + Zn @ 5 kg/ha applied to soybean only was found most productive (2625 kg/ha soybean equivalent yield) and remunerative (Rs 9944/ha additional returns). The corresponding values for control (no organic manure) across fertility levels were 2035 kg/ha and Rs 5922/ha, respectively. However, application of famyard manure @ 5 tonnes/ha showed the highest net energy output (6576 MJ/ha), energy-use efficiency (l.23), energy productivity (83.62 g/MJ) and incremental benefit: cost ratio (0.88). Application of soybean residue @ 5 tonnes/ha was most energy-intensive (1.12 MJ/Rs). Yield and economical parameters increased linearly as levels of fertility increased while reverse trend was observed with energy-use efficiency, energy productivity and energy intensiveness. The maximum net energy output (4998 MJ/ha) was recorded with 50% of recommended level of fertilizers.